PENGARUH GAYA HIDUP DAN TINGKAT LITERASI KEUANGAN TERHADAP PENGGUNAAN PAYLATER PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS JAMBI - Delvi Yani, Evi; Arpizal; Wahyuni, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of lifestyle and financial literacy levels on Paylater usage among economics education students at the Faculty of Teacher Training and Education, University of Jambi, both partially and simultaneously. This study uses a quantitative approach with an ex-post facto method. The population in this study were economics education students from the classes of 2023, 2024, and 2025, with a sample of 117 respondents using a purposive sampling technique. Data collection used a closed questionnaire via Google Form. The data analysis technique used was descriptive statistical analysis. The results of the study indicate that partially the lifestyle variable has a positive and significant influence on Paylater usage with a calculated t value > t table. Partially, the level of financial literacy on Paylater usage has a negative and insignificant influence with a calculated t value < t table. Simultaneously, lifestyle and financial literacy levels have a positive and significant influence on Paylater usage.